(untitled) - Shi, David E. (New York, 1999)
For The Record: A Documentary History of America is a rich resource with over 300 primary source readings from diaries, journals, newspaper articles, speeches, government documents, and novels. This ancillary has been updated to mirror Tindall and Shi's America: A Narrative History's contents, making it easy to assign readings that enrich discussions in the text.
Keywords: United states; History,Sources